Analysis of frequency of congenital fetal anomalies diagnosed on antenatal ultrasound in a tertiary care hospital of Balochistan - Jesrani, Ameet; Gul, Pari; Jogezai, Shama; Gul, Palwasha; Naheed, Fahmida; Jamal, Asif (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: The objective of our study is to check the incidence of various congenital fetal anomalies in antenatal period by ultrasonography in a subset of population. Methods: This cross sectional study was conducted in the department of Radiology, Bolan Medical Complex Hospital Quetta from November 2017 to October 2018. Total of 1323 second and third trimester pregnancies were analyzed for a period of one year. 34 fetal anomalies were detected making the prevalence of 2.5%. Information obtained from history, clinical examination and Ultrasound examination were recorded. The data was analyzed in SPSS 20.These patients were also interviewed for folic acid supplementation and consanguineous marriage. Results: 1323 patients were examined with congenital abnormalities detected in 34 fetuses. Among 34 fetuses, 20 were male and 14 were female fetuses. Out of 34, mother of 24 fetuses verified that they did not take folic acid supplementation. Consanguineous marriage recognized as the important risk factor as found in 22 congenital abnormal fetus. CNS anomalies were the most commonly occurring anomalies with prevalence of (0.9%) followed by gastrointestinal tract anomalies (0.3%) and Urinary tract anomalies (0.3%). Conclusions: The fetus prognosis largely depends on early detection of its any congenital anomaly on antenatal ultrasound as they can result in abortions, still births and other fetal defects. So antenatal ultrasound is very important and safe method for early detection and management of fetal anomalies.